Alcohol-to-acid ratio and substrate concentration affect product structure in chain elongation reactions initiated by unacclimatized inoculum. (October 2016) - Liu, Yuhao; Lü, Fan; Shao, Liming; He, Pinjing
Highlights: High alcohol to acid ratios and substrate concentrations improved efficiency of CE. The structures and yields of products were influenced by the alcohol to acid ratio. Odd-carbon-number carboxylates were generated in non-negligible quantities. A shorter reaction period is beneficial when using a lower alcohol to acid ratio. Protein-rich bio-waste can serve as a carbon source for heptanoate production. Abstract: The objective of the study was to investigate whether the ratio of ethanol to acetate affects yield and product structure in chain elongation initiated by unacclimatized mixed cultures. The effect of varying the substrate concentration, while maintaining the same ratio of alcohol to acid, was also investigated. With a high substrate concentration, an alcohol to acid ratio >2:1 provided sufficient electron donor capacity for the chain elongation reaction. With an ethanol to acetate ratio of 3:1 (300 mM total carbon), the highest n -caproate concentration (3033 ± 98 mg/L) was achieved during the stable phase of the reaction. A lower substrate concentration (150 mM total carbon) gave a lower yield of products and led to reduced carbon transformation efficiency compared with other reaction conditions. The use of unacclimatized inoculum in chain elongation can produce significant amounts of odd-carbon-number carboxylates as a result of protein hydrolysis.